2014
DOI: 10.1111/ppc.12059
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Nursing Care for Adult Survivors of Child Maltreatment: A Systematic Review of the Literature

Abstract: Psychiatric nurses need training in how to assess a history of child abuse and the late-life consequences of abuse in adult psychiatric patients. They also need to be trained to respond effectively to these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Despite a reluctance to address CSA, participants demonstrated an awareness about key interpersonal skills needed to support survivors, with empathy, active listening, and adopting a nonjudgmental approach guiding conversations. This corresponds with the extant literature (van der Zalm et al, 2015 ), indicating that psychiatric nurses are more prepared than they realize to engage with survivors and hold the necessary skill sets to develop meaningful therapeutic relationships. However, the perceived lack of confidence around using these skills needs to be addressed.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Despite a reluctance to address CSA, participants demonstrated an awareness about key interpersonal skills needed to support survivors, with empathy, active listening, and adopting a nonjudgmental approach guiding conversations. This corresponds with the extant literature (van der Zalm et al, 2015 ), indicating that psychiatric nurses are more prepared than they realize to engage with survivors and hold the necessary skill sets to develop meaningful therapeutic relationships. However, the perceived lack of confidence around using these skills needs to be addressed.…”
Section: Discussionsupporting
confidence: 83%
“…While it is imperative that psychiatric nurses act in an altruistic fashion (Başoğul et al, 2019 ; Deborah et al, 2020 ), nurses also need to be aware that survivors' healing journeys can be best facilitated by developing meaningful therapeutic connections with others (Azzopardi et al, 2021 ; Easton et al, 2015 ; Sivagurunathan et al, 2019 ). In the absence of such discussions, or where CSA is ignored, van der Zalm et al ( 2015 ) found that nurses may actually risk causing harm to survivors. Considering how central the development of therapeutic relationships is the role of the role of the psychiatric nurse, nurses need to be made more aware of the potential positive influence they can have on survivors by exploring their trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, psychiatric nurses remain poorly confident about how to respond properly to trauma survivors (van der Zalm, Nugteren, Hafsteinsdottir, van der Venne, Kool, & van Meijel, 2015).…”
mentioning
confidence: 99%